L'adaptation de chanson dans l'album ”Cœur vagabond” de Bïa. Une brise de Brésil - Abbrugiati, Perle (ATeM – Archiv für Textmusikforschung, 2019)
Perle Abbrugiati's article explores Coeur vagabond/Coraçao vagabundo, the fourth record by the French-Brazilian artist Bïa, released in 2006. The bilingual album comprises an equal number of Brazilian-Portuguese adaptations from French songs and French adaptations from Brazilian songs. The aim of the present article is to identify the strategies applied in the translation of songs. To this end, the article's author herself uses translation within the framework of a comparative approach, confronting Bïa's translations with her own literal translations (not suitable to be sung) of the original lyrics. The objective is not to trace 'mistranslations' but to point out in how many different and intricate ways a translation can be faithful while being creative, and in what way and to what degree the song translator may take the liberty of 're-semantisation'.
Keywords: Chanson; traduction

“Where You Are Accepted, You Blossom”: Toward Care Ethics in Jazz Historiography - Blais-Tremblay, Vanessa (Jazz & Culture, 2019)
Publisher: University of Illinois Press

“Portrait en Noir et Blanc”: Chico Buarque em francês por Bïa Krieger [“Portrait en Noir et Blanc”: Chico Buarque en français par Bïa Krieger] - Cassiano, Raissa Conde (Tradução em Revista, 2019)

Musical Geographies and Iconic Music Legends: Mapping Céline Dion's Outstanding Contribution to Music and Global Popular Music Culture - Jucu, Ioan-Sebastian (Territorial Identity and Development, 2019)
Between music geography and iconic music legends, a strong connection has been established in terms of spatial and temporal analysis of popular music and the representation of national identities in the contemporary global cultures of popular music. The existing literature unveils a gap in the analysis of music geography and famous musicians, real global music icons identified with particular cultures. This paper argues that such music legends must be geographically studied to unveil their outstanding contribution to the world music cultures. Against such a background, a geographical approach that takes Canadian singer Céline Dion as a case studyis developed. The research aims to analyse Dion’s outstandingcontribution to global music culture in both spatial and temporal terms. Based on the music industry emergence, the paper focuses on how and why Céline Dion appeared in global music culture and examines her outstanding contribution with specific referenceto music cartographies and statistical research.National identity and related cultural issues beyond the music, lyrics, and performances are also addressed.The empirically led study is based on a multi-method approach and makes use of statistical data analysis, GIS methods, biographicalinquiry, the analysis of lyrics and visual methodologies,all suggesting that Dion’s contribution has greatly influenced the global popular music culture of the last few decades.Although the topics in question cannot be fully discussed within the limits of this paper, it highlights the importance of these issues and calls for further in-depth research to provide a new critical understanding of the intimate connections between popular music, legendary music icons and the recent perspectives in music geographies

Ton métier, le mien, le Québec. Fragments de correspondance amoureuse et politique 1962-1993 - Julien, Pauline; Godin, Gérald (Leméac Éditeur, 2019)
Dix ans après la parution de La renarde et le mal peigné,quatre cents nouvelles lettres échangées entre Gérald Godin (1938-1994) et Pauline Julien (1929-1998) ont été découvertes dans leurs fonds d’archives respectifs. Soixante-dix d’entre elles ont été choisies par Emmanuelle Germain et Jonathan Livernois, dans cette édition qui vient compléter le portrait forgé en 2009. On y retrouvera les débuts de la relation entre le journaliste et la chanteuse, les longues tournées en Europe de Pauline Julien, la maladie de Godin, puis celle, en filigrane, de Julien. De nouveaux aspects apparaîtront également : l’érotisme de plusieurs de leurs échanges ; les rapports d’amitié ; les aléas d’une vie familiale où un jeune homme de vingt-cinq ans doit s’occuper de deux adolescents, alors que Julien doit concilier sa vie professionnelle et sa vie de mère ; l’épuisement des dernières années, tandis que les tournées européennes sont de plus en plus difficiles pour Julien. Les lettres réunies ici permettront également aux lectrices et aux lecteurs de revivre de grands moments de l’histoire québécoise, vue à la hauteur de ses acteurs : le « Vive le Québec libre ! » lancé par Pauline Julien à Niamey, en 1969, interrompant le ministre fédéral Gérard Pelletier ; la crise d’Octobre et l’emprisonnement sur lequel on ne reviendra guère ; la campagne électorale de 1976, l’enthousiasme et la victoire, inattendue ; l’engagement du député puis ministre Gérald Godin. Ce n’est donc pas un hasard si ce petit livre est sous-titré « Fragments de correspondance amoureuse et politique ». La suture des deux univers, de l’intime et du public, de l’amour et du politique, y est plus claire que jamais.